Increased serum fibroblast growth factor 21 levels are associated with adverse clinical outcomes after intracerebral hemorrhage - Chen, Keyang; Huang, Wenting; Wang, Jing; Xu, Huiqin; Ruan, Lixin; Li, Yongang; Wang, Zhen; Wang, Xue; Lin, Li; Li, Xiaokun (Frontiers in Neuroscience, 2023)
Introduction Intracerebral hemorrhage (ICH) is the most prevalent cause of death. We sought to explore whether serum Fibroblast growth factor 21 (FGF21) is of substantial benefit in predicting poor prognosis in ICH patient. Methods A prospective, multicenter cohort analysis of serum FGF21 levels in 418 ICH patients was carried out. At three months following ICH start, the primary endpoint was death or major disability, whereas the secondary endpoint was death. We investigated the association between serum FGF21 and clinical outcomes. We added FGF21 to the existing rating scale to assess whether it enhanced the prediction ability of the original model. Effectiveness was determined by calculating the C-statistic, net reclassification index (NRI), absolute integrated discrimination improvement (IDI) index. Results Among 418 enrolled patients, 217 (51.9%) of the all subjects had death or significant disability. Compared with patients in the lowest quartile group, those in the first quartile group had higher risk of the primary outcome (Odds ratio, 2.73 [95%CI,1.42–5.26, p < 0.05]) and second outcome (Hazard ratio, 4.28 [95%CI,1.61–11.42, p < 0.001]). The integration of FGF21 into many current ICH scales improved the discrimination and calibration quality for the integrated discrimination index’s prediction of main and secondary findings (all p < 0.05). Conclusion Elevated serum FGF21 is associated with increased risks of adverse clinical outcomes at 3 months in ICH patients, suggesting FGF21 may be a valuable prognostic factor.